Study of Non-Performing Assets in Public and Private Sector Banks in the New Age of Technology: Examining the impact of technology on non-performing assets in Indian banks (Journal of Advances and Scholarly Researches in Allied Education, 2016)
Banking industry is considered as the backbone of Indian economy. After liberalization of the policies by the government, the banks have to be more competitive and performance-oriented in the new environment. In this study we analyzed financial liberalization and banking performance of private sector banks in India. India has over the last decades experienced different degrees of repressive policies in the banking sector. This study attempts to examine the changes in the productive efficiency of Indian commercial banks after financial sector reforms. Non-performing assets are one of the major concerns for banks in India. NPAs reflect the performance of banks. A high level of NPAs suggests high probability of a large number of credit defaults that affect the profitability and net-worth of banks and also erodes the value of the asset. NPAs affect the liquidity and profitability, in addition to posing threat on quality of asset and survival of banks.